Towards the Development of Salt Tolerant Rice Varieties by Overexpressing cDNAs From A Mangrove Plant Acanthus Ebracteatus Vahl - Sultana, Shahanaz (2010)
Rice (Oryza sativa L.) is one of the most important cereal crops in the world. Environmental stresses such as salinity are important limiting factors for crop growth and yield. Rice is a salt-sensitive crop that suffers salinity stress from germination to maturity, resulting in very poor yield. Rice varieties with high yield and tolerance to salt have to be developed to enable cultivation of rice plant on saline area. Two cDNAs encoding monodehydroascorbate reductase (AcMDHAR) and 9-cis-epoxycarotenoid dioxygenase (AcNCED) were previously isolated from a mangrove plant, Acanthus ebracteatus. These enzymes were reported to be involved in different salt tolerance mechanisms in plants. Monodehydroascorbate reductase (MDHAR), an important enzyme in the ascorbate-glutathione cycle, is involved in the salt tolerance mechanism of plants through scavenging of reactive oxygen species (ROS). While NCED is an important enzyme in the oxidative cleavage reaction of abscisic acid (ABA), a plant iv hormone which plays a vital role in stress tolerance. In this study, two overexpression vectors, pEXP32-AcMDHAR and pEXP32-AcNCED; were constructed using Gateway® technology and transformed into Taipei 309 and BRRI dhan29 rice varieties through Agrobacterium-mediated transformation, respectively. The putative transformants overexpressing AcMDHAR and AcNCED were selected in vitro using hygromycin and confirmed by PCR screening. The copy number of AcMDHAR in transgenic rice plants, ranged from single to multiple copies which was determined by real time PCR. The abundance of transcripts in transgenic rice plants was also analyzed by real time PCR. Transgenic rice plants overexpressing AcMDHAR treated at 100 mM NaCl showed significant increase in MDHAR enzyme activity compared to untransformed (UT) plants and showed tolerance to salt at germination, seedling and reproductive stages. These results implied that the overexpression of AcMDHAR in rice can enhance tolerance to salt through the increase of MDHAR enzyme activity. None of the rice plants overexpressing AcNCED showed tolerance to salt although expression was detected by real time PCR. The levels of ABA, in transgenic rice plants overexpressing AcNCED treated with 100 mM NaCl for 24 hours were similar to those in NaCl - treated UT plants. In contrast, higher levels of phaseic acid (PA), dihydrophaseic acid (DPA) and ABA- glucose ester (ABA-GE) were observed in rice plants overexpressing AcNCED compared to UT plants, indicating that ABA has been converted to PA, DPA and ABA-GE rapidly in the transgenic rice plants. These results suggested that the rapid degradation of excess ABA through self regulatory mechanisms may have caused the failure of these transgenic rice plants to exhibit salinity tolerance. v The findings of this study have provided important information towards the gene manipulation and the development of salt tolerant transgenic rice.